2010
DOI: 10.1111/j.1475-097x.2010.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of differential oscillometric device with invasive mean arterial blood pressure monitoring in intensive care patients

Abstract: Non-invasive beat-to-beat mean arterial pressure (MAP) in finger arteries recorded by the differential oscillometric device was compared with MAP recorded invasively from A. radialis in 22 patients after cardiac surgery. Based on all 132 paired measurements, the MAP values measured at the radial artery were 2.7 ± 4.9 mmHg higher than those measured on fingers. Among 22 patients there were 8 patients receiving inotropic support, their difference being 2.1 ± 5.6 mmHg. The present study revealed that the mean dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, several studies found that BP measurement in the brachial artery by both intra-arterial and auscultatory methods provided different results [27]. Moreover, comparisons of radial IBP with wrist or finger OBP did not produce uniform results, as expected [19, 22, 23, 33]. Unfortunately, in clinical practice decisions are often based on the BP values that are available, regardless of the method (NIBP or IBP) or the site (radial or brachial artery) where BP is detected.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, several studies found that BP measurement in the brachial artery by both intra-arterial and auscultatory methods provided different results [27]. Moreover, comparisons of radial IBP with wrist or finger OBP did not produce uniform results, as expected [19, 22, 23, 33]. Unfortunately, in clinical practice decisions are often based on the BP values that are available, regardless of the method (NIBP or IBP) or the site (radial or brachial artery) where BP is detected.…”
Section: Discussionmentioning
confidence: 86%
“…This may result in greater risks of erroneous clinical decisions—for example, unnecessary use of inotropic support and blood transfusions in hypotensive patients or, conversely, delayed antihypertensive treatment in hypertensive patients [13, 19, 28]. Unfortunately, the literature is not consistent about the range of accuracy that can be considered acceptable in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen articles [25][26][27][28][29][30][31][32][33][34][35][36][37] were excluded after full-text review for failure to meet the inclusion criteria or insufficient data for meta-analysis (appendix 3). The remaining 28 studies [8][9][10][11][12][13][14][15][16][17][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were included in the systematic review (fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…This tool was developed by the researchers after reviewing the related literature (16)(17)(18)(19)(20)(21)(22) . The tool was utilized to assess definite items related to MAP.…”
Section: Toolmentioning
confidence: 99%